Biohidrogenação ruminal e digestão de ácidos graxos em ovinos alimentados com dietas contendo óleos de babaçu ou buriti - MACHADO, Nítalo André Farias (2018)
The objective was to estimate biohydrogenation (RBH) and apparent digestibility (Dap) of fatty acids (AG) of sheep fed with diets contained babassu and buriti oil. Twenty-one sheep Dorper ˣ Santa Inês, castrated, with six months of age and average live weight of 26 ± 4 kg with distributed in incomplete block design. Experimental diets consisted of three: control diet, without addition of oil (CON), addition of 4% (diet% DM) of babassu oil (OBA), and addition of buriti oil (OBU). The experiment was carried out for 18 days, 15 days for the adaptation of the animals to the experimental diets and 3 days for sampling the food offered, leftovers and feces. After the experiment was finished, the animals were slaughtered and the abomasum contents were collected. The AG of dietary ingredients, faeces and abomasum were determined by gas chromatography. The balance between the AG profile of the diet and abomasum estimated the BHR of the oleic, linoleic and linolenic AG and the complete BHR. The Dap was calculated by the ratio between the amount of AG ingested and excreted in the faeces. The analysis of the data was performed by orthogonal contrasts, being: 1) control diet versus diet containing 40 g/kg DM of oils, and 2) babassu oil versus oil buriti). Differences were considered significant when P<0.05. Inclusion of vegetable oils increased (P<0.05) the RBH of oleic acid. The Inclusion of vegetable oils increased (P<0.05) the RBH of oleic acid. However, it reduced (P<0.05) the RBH of the linoleic and linolenic acids, and increased the Dap of the AG of the diets, especially in OBA. Additionally, OBA promoted lower RBH of linolenic acid and complete RBH, with increased concentration of intermediates of RBH with trans geometric configuration and polyunsaturated fatty acids, when compared to OBU, which in turn increased the complete BHR, with consequent production of stearic acid (C18:0). The addition of babassu oil reduces the complete ruminal biohydrogenation of unsaturated fatty acids, generating a higher concentration of intermediate fatty acids from biohydrogenation, and increases the total digestibility of fatty acids, an interesting factor for sheep meat quality.